OPTY-LINE remote-controlled adjustable intramedullary device implantation in open-wedge high tibial osteotomy: A prospective proof-of-concept pilot and comparison with Tomofix fixed-plate device method. (1st August 2019) - Jonker, Leon; Fallahi, Farshid; Saraswathy, Jayadeep J; Edge, John; Dawson, Matt
Purpose: The objective was to evaluate the clinical and patient-related short- to medium-term performance of the OPTY-LINE nail device for high tibial osteotomy (HTO), comparing a case series of the said device to the established Tomofix fixed-plate device. Patients and Methods: Males with symptomatic medial compartmental osteoarthritis and no serious (co-morbid) knee pathology were followed up, five Tomofix and six OPTY-LINE patients. Patients underwent computed tomography assessment and completed Knee Injury and Osteoarthritis Outcome score (KOOS) and osteotomy surgery patient satisfaction questionnaires, 3 and 6 months post-surgery. A radiologist impression score and a quantitative digital bone density analysis were performed by two independent radiologists. Mann–Whitney U test was applied for inferential statistical tests. Results: At 6 months post-surgery, for Tomofix, the median radiologists' healing impression score was 'progressive healing' versus 'union virtually complete' for the OPTY-LINE nail; bone healing quotient was 1.30 (standard deviation (SD) 1.74) versus 1.78 (SD 1.58), p = 0.18. The post-operative absolute surgical accuracy was a mean 12 (7.5) for Tomofix versus 4.1 (2.3) for OPTY-LINE, p = 0.052. At baseline, however, Tomofix patients had more knee symptoms, as determined by KOOS symptom sub-score, when compared to the OPTY-LINE cohort ( p = 0.009). Conclusion: This initial, non-randomized, comparative evaluation of the OPTY-LINE device for HTO has produced similar outcomes to patients treated with the established Tomofix device. In particular, the rate of post-surgical bone regeneration and surgical accuracy achieved with the OPTY-LINE device are encouraging. Large-scale randomized controlled studies with longer follow-up are indicated to further evaluate the clinical and patient-related outcome performance for OPTY-LINE.